5.3 Allergy and Immunology 2015
DOI: 10.1183/13993003.congress-2015.pa1087
|View full text |Cite
|
Sign up to set email alerts
|

IL-25 induces airways angiogenesis and expression of multiple angiogenic factors in a murine asthma model

Abstract: Background: Th2-promoting cytokine IL-25 might contribute to bronchial mucosal vascular remodelling in asthma through its receptor expressed by vascular endothelial and vascular smooth muscle cells. Methods: By utilising a newly established chronic asthma murine model induced by direct exposure of the airways to IL-25 alone, we examined effects of IL-25 on angiogenesis, vascular remodelling and expression of angiogenic factors, compared changes with those in a "classical" ovalbumin (OVA)-induced murine asthma … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…VWF , a large plasma glycoprotein, plays a vital role in mediating the balance between blood clotting and bleeding [ 36 ]. A study by Yao et al [ 37 ] showed that VWF was highly expressed in an IL-25-induced murine asthma model and was associated with bronchial mucosal vascular remodeling in asthma. LAMB3 and LAMA4 belong to the laminin subunit family and have been reported to be involved in the metastasis and invasion of some types of cancer [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…VWF , a large plasma glycoprotein, plays a vital role in mediating the balance between blood clotting and bleeding [ 36 ]. A study by Yao et al [ 37 ] showed that VWF was highly expressed in an IL-25-induced murine asthma model and was associated with bronchial mucosal vascular remodeling in asthma. LAMB3 and LAMA4 belong to the laminin subunit family and have been reported to be involved in the metastasis and invasion of some types of cancer [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a chronic murine model established in our laboratory demonstrated that intranasal exposure to IL‐25 up to 2 months mimicked OVA‐induced or house dust mite‐induced asthma‐like changes . Interestingly, this model manifested asthma‐like but allergen‐independent acute and chronic inflammation and structural changes of remodelling in the airways, including eosinophilia, predominant expression of Th2‐type cytokines, AHR, goblet cell hyperplasia, sub‐epithelial collagen deposition, smooth muscle hyperplasia/hypertrophy and angiogenesis . However, although IL‐25 can directly induce the proliferation and expression of collagen I/III and smooth muscle alpha‐actin by primary human lung fibroblasts and can induce angiogenesis in vitro by directly acting on HUVECs we still cannot exclude the indirect role of IL‐25 on fibrosis and angiogenesis of asthmatic airways by affecting the expression of Th2 cytokines originated from other immune cells.…”
Section: Il‐25 and Asthma: Emerging Evidence From Human And Animal Stmentioning
confidence: 84%
“…61 Interestingly, this model manifested asthma-like but allergen-independent acute and chronic inflammation and structural changes of remodelling in the airways, including eosinophilia, predominant expression of Th2-type cytokines, AHR, goblet cell hyperplasia, subepithelial collagen deposition, smooth muscle hyperplasia/hypertrophy and angiogenesis. [61][62][63] However, although IL-25 can directly induce the proliferation and expression of collagen I/III and smooth muscle alpha-actin by primary human lung fibroblasts and can induce angiogenesis in vitro by directly acting on HUVECs we still cannot exclude the indirect role of IL-25 on fibrosis and angiogenesis of asthmatic airways by affecting the expression of Th2 cytokines originated from other immune cells. Nevertheless, the above-mentioned and other in vivo animal studies, using overexpression or depletion methods, provide solid evidence supporting a critical role of IL-25 in the development of airway inflammation and remodelling of asthma.…”
Section: Il-25 Is a Pleiotropic Cytokine In Modulating Allergen-depenmentioning
confidence: 99%
“…35 Yao et al demonstrated that the chronic exposure of murine airways to IL-25 alone is able to increase reproduction of a local angiogenic milieu, as well as cause functional airway remodeling. 36,37 Numerous studies have demonstrated solid evidence in support of a critical role of IL-25 in the development of airway inflammation and asthma remodeling. 38,39 Studies in mouse models have also shown that IL-25 and type 2 innate lymphoid cells can result in the induction of pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%